2023
DOI: 10.1021/acsnano.3c01758
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of Hollow Covalent Organic Frameworks: Synthesis and Applications

Abstract: Hollow covalent organic frameworks (COFs) have gained significant attention because of their specific properties, including enhanced surface-to-volume ratio, large surface area, hierarchical structure, highly ordered nanostructures, and excellent chemical stability. These intrinsic characteristics endow hollow COFs with fascinating physicochemical properties and make them highly attractive for widespread applications, such as catalysis, energy storage, drug delivery, therapy, sensing, and environmental remedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 115 publications
(387 reference statements)
0
11
0
Order By: Relevance
“…In addition, it has been shown that DESs possess the ability to undergo recycling and serve as a structural template for the synthesis of distinct COFs including layered pore topologies that are unattainable using conventional solvothermal methods. [120] Although there are some advantages associated with the use of these media, the viscosity of the media poses a substantial constraint on the successful synthesis of COF. Moreover, the utilisation of this synthesis methodology is presently restricted to certain COFs, hence limiting its overall applicability.…”
Section: Synthesis Of Cofs In a Novel Reaction Mediummentioning
confidence: 99%
“…In addition, it has been shown that DESs possess the ability to undergo recycling and serve as a structural template for the synthesis of distinct COFs including layered pore topologies that are unattainable using conventional solvothermal methods. [120] Although there are some advantages associated with the use of these media, the viscosity of the media poses a substantial constraint on the successful synthesis of COF. Moreover, the utilisation of this synthesis methodology is presently restricted to certain COFs, hence limiting its overall applicability.…”
Section: Synthesis Of Cofs In a Novel Reaction Mediummentioning
confidence: 99%
“…10–13 As another new class of popular porous materials, covalent organic frameworks (COFs) have received significant interest as adsorbents in environmental analysis, catalysis, and energy storage in recent years due to their ultra-high specific surface area, tunable pore size, abundant functional groups, and easy surface functionalization. 14–17 However, most COFs are produced in the powder form, which makes them difficult to separate and recover from water after adsorption. 18 In recent years, researchers have developed several methods to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent–organic frameworks (COFs), as a kind of porous crystalline frameworks, have received increasing attention in the field of photocatalysis due to their excellent visible light response ability, high porosity for substrate adsorption, extended π-conjugated structures for efficient separation of photogenerated carriers, and improved stability. In addition, the diversity of construction units and a reversible covalent bond endow COFs with a designed crystalline ordered structure and tunable bandgap positions, which makes COFs very attractive photocatalysts. Various COFs with conjugated structures and building units have been reported as efficient photocatalysts for organic oxidation, such as triazine-functionalized sp 2 -carbon COFs, , benzoxazole-linked COFs, and hydrazone-linked 2D porphyrinic COFs . Among various COFs, imine-based COFs formed by the condensation of aldehydes with amines have become the most widely investigated photocatalysts because of their easy formation, conjugated structure, and excellent visible light response .…”
Section: Introductionmentioning
confidence: 99%